Local wisdom: As a primary approach to maintaining beach cleanliness and ecosystem sustainability - Kaswandi Kaswandi; Fayyaza Adiela; Mansyah Muh Sutri; Karim La Ode Muhammad; Priadi Revalina Nur Aliyah (BIO Web of Conferences)
Local wisdom is a cultural heritage that reflects the values, norms, and traditions developed within a society as a form of harmony between humans and the environment. In the context of maintaining beach cleanliness and ecosystem sustainability, local wisdom becomes a highly relevant and effective primary approach. This study aims to identify and analyze the role of local wisdom in coastal preservation and sustainable ecosystem management. The community service activity involved delivering lectures to the residents of Gumanano Village, Central Buton Regency. The results indicate that the values upheld by the Gumanano Village community, such as the spirit of mutual cooperation, customary prohibitions against environmentally destructive behaviors, and rituals honoring the sea, play a crucial role in maintaining beach cleanliness and ecological balance. Moreover, the synergy between local wisdom and government policies has the potential to create an inclusive and sustainable environmental management model. Thus, local wisdom serves not only as a moral guide but also as a practical strategy that can be integrated into coastal conservation and community education programs. In conclusion, strengthening local wisdom through multisectoral collaboration is a strategic step toward achieving sustainable beach and ecosystem preservation.